2011
DOI: 10.1371/journal.pone.0017986
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Helicobacter pylori Protease HtrA Found by ‘Virtual Ligand’ Screening Combat Bacterial Invasion of Epithelia

Abstract: BackgroundThe human pathogen Helicobacter pylori (H. pylori) is a main cause for gastric inflammation and cancer. Increasing bacterial resistance against antibiotics demands for innovative strategies for therapeutic intervention.Methodology/Principal FindingsWe present a method for structure-based virtual screening that is based on the comprehensive prediction of ligand binding sites on a protein model and automated construction of a ligand-receptor interaction map. Pharmacophoric features of the map are clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…We have developed the inhibitor HHI for HpHtrA (15) that impaired E-cadherin degradation and epithelial barrier (4). On the basis of our data, we concluded that specific inhibition of HtrAs from different pathogens requires highly selective compounds.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We have developed the inhibitor HHI for HpHtrA (15) that impaired E-cadherin degradation and epithelial barrier (4). On the basis of our data, we concluded that specific inhibition of HtrAs from different pathogens requires highly selective compounds.…”
Section: Discussionmentioning
confidence: 85%
“…We described the first functional inhibitor HHI targeting HpHtrA (15) to prevent E-cadherin shedding and the paracellular transmigration of H. pylori (4). To test whether HHI also inhibits HtrA from other Gram-negative bacteria, we performed in vitro E-cadherin cleavage experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, given the crucial role of HtrA in virulence in numerous pathogenic organisms, this protease is an attractive target for antibiotic development. Using structure-based virtual screening, Lower et al 99 found a set of compounds that had the potential to act as small-molecule inhibitors of H. pylori HtrA, the enzyme that cleaves host E-cadherins. Out of the 22 compounds retrieved from virtual screening, 6 were shown to inhibit cleavage of E-cadherins by H. pylori HtrA in an in vitro proteolysis assay.…”
Section: Clp Proteasementioning
confidence: 99%
“…Previously, proteolytic cleavage of E-cadherin was linked to the malignant progression of adenocarcinomas (35,44). By using a virtual screening approach, Lower et al (91) identified inhibitors of HtrA that may help prevent bacterial infiltration of the epithelium.…”
Section: A Strategy To Effect H Pylori Clearance By the Immune Responsementioning
confidence: 99%